Pengaruh Kualitas Jaringan, Harga Dan Promosi Terhadap Keputusan Pembelian Paket Data Xl Axiata Melalui Minat Beli Sebagai Variabel Intervening (Studi Kasus: Pengguna Xl Axiata Di Kabupaten Jember) - Siti Habibah Maslahah; Hary Sulaksono; Hamzah Fansuri Yusuf (JMBI : Jurnal Manajemen Bisnis dan Informatika, 2022)
This study entitled "The Effect of Network Quality, Price and Promotion on XL Axiata Data Card Purchase Decisions through Purchase Interest as an Intervening Variable (XL Axiata Case study of XL Axiata users in Jember Regency)". This study aims to determine the direct and indirect effect of Network Quality, Price and Promotion on XL Axiata Data Card Purchase Decisions through Purchase Interest as Intervening Variable in Jember Regency. The population of this study are people who have used XL Axiata in Jember. The sample used was 50 respondents. The sampling technique using Non-Probability Sampling is Accidental Sampling. The data analysis method used path analysis with the help of SPSS 25. Data analysis used data instrument tests (validity test and reliability test), classical assumption test (normality test, multicollinearity and hiteroscedasticity test), Sobel test, coefficient of determination, t test and F test. Results The research shows that there is a direct effect of the network quality variable on buying interest, while for the price and promotion variables there is no direct effect on buying interest. For a direct influence on purchasing decisions, there is a direct influence of buying interest variables on purchasing decisions, while network quality, price and promotion have no direct effect. For the indirect effect of the network quality variable, it is stated that it has an indirect effect on purchasing decisions through buying interest. While prices and promotions do not have an indirect influence on purchasing decisions through buying interest.